Effect of elevated CO2 on the dynamics of particle-attached and free-living bacterioplankton communities in an Arctic fjord - S. Romac; U. Riebesell; J. I. Nissimov; L. Bittner; J. Gilbert; J. La Roche; A.-S. Roy; H. Schunck; A. Wichels; G. Gerdts; J. Piontek; M. Sperling; et al. (Biogeosciences, 2013)
In the frame of the European Project on Ocean Acidification (EPOCA), the response of an Arctic pelagic community (<3 mm) to a gradient of seawater pCO2 was investigated. For this purpose 9 large-scale in situ mesocosms were deployed in Kongsfjorden, Svalbard (78°56.2´ N, 11°53.6´ E), in 2010. The present study investigates effects on the communities of particle-attached (PA; >3 μm) and free-living (FL; < 3 μm > 0.2 μm) bacteria by Automated Ribosomal Intergenic Spacer Analysis (ARISA) in 6 of the mesocosms, ranging from 185 to 1050 μatm initial pCO2, and the surrounding fjord. ARISA was able to resolve, on average, 27 bacterial band classes per sample and allowed for a detailed investigation of the explicit richness and diversity. Both, the PA and the FL bacterioplankton community exhibited a strong temporal development, which was driven mainly by temperature and phytoplankton development. In response to the breakdown of a picophytoplankton bloom, numbers of ARISA band classes in the PA community were reduced at low and medium CO2 (~ 185–685 μatm) by about 25%, while they were more or less stable at high CO2 (~ 820–1050 μatm). We hypothesise that enhanced viral lysis and enhanced availability of organic substrates at high CO2 resulted in a more diverse PA bacterial community in the post-bloom phase. Despite lower cell numbers and extracellular enzyme activities in the post-bloom phase, bacterial protein production was enhanced in high CO2 mesocosms, suggesting a positive effect of community richness on this function and on carbon cycling by bacteria.